2008
DOI: 10.1007/s10499-007-9162-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulating influence of herbal biomedicines on nonspecific immunity in Grouper Epinephelus tauvina juvenile against Vibrio harveyi infection

Abstract: Herbals such as Cynodon dactylon, Piper longum, Phyllanthus niruri, Tridax procumbens, and Zingiber officinalis were extracted with acetone, benzene, butanol, and petroleum ether and screened against the pathogen Vibrio harveyi isolated from the infected Grouper Epinephalus tauvina. Among the different solvent extractions screening to V. harveyi, petroleum ether extracts were suppressed significantly (P \ 0.05). Equal proportions of the all-plant extracts were mixed with the artificial feeds at concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(66 citation statements)
references
References 19 publications
4
58
0
4
Order By: Relevance
“…Previously, enhancement of phagocytic and NBT activities following administration of herbal products in fish species have been reported in a number of studies (Rao et al 2006;Sahu et al 2007;Punitha et al 2008;Pratheepa et al 2010;Sharma et al 2010;Behera et al 2011;Uthayakumar et al 2014b;Anusha et al 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Previously, enhancement of phagocytic and NBT activities following administration of herbal products in fish species have been reported in a number of studies (Rao et al 2006;Sahu et al 2007;Punitha et al 2008;Pratheepa et al 2010;Sharma et al 2010;Behera et al 2011;Uthayakumar et al 2014b;Anusha et al 2014).…”
Section: Discussionmentioning
confidence: 96%
“…The IgY edible antibody, produced with the herbal adjuvant Asparagus racemosus, is a good vaccine candidate for improving serum bactericidal activity against white-spot symdrome virus (WSSV) infection in Penaeus monodon (Kumaran et al 2010). Herbal immunostimulants also enhanced the serum bactericidal and lysozyme activity against Vibrio harveyi infection in grouper Ephinephelus tauvina (Sivaram et al 2004, Punitha et al 2008). The increased A:G ratio in vaccine-treated groups in our study indicated higher immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…CC eluted HF2 of HEUD exhibited more antibacterial activity as compared to other subfractions in disc diffusion assay. The extracts and fractions can be considered active when the MIC is less than 100 μg/mL (Punitha et al, 2008).…”
Section: Discussionmentioning
confidence: 99%